Mengungkap Pola Hubungan Antara PDB dan Pendapatan Domestik Pemerintah di Indonesia - Okta Irawati; Pascal Ismail; Najwa Masayu Azzahra; Dwi Fitria Alfiani; Ario Isnandar; Muhammad Naufal Arif (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
Gross Domestic Product (GDP) and domestic government revenue are two important indicators that reflect the condition and stability of a country's economy. In Indonesia, understanding the relationship between these two indicators is highly relevant, especially in assessing the success of fiscal policy and the direction of national development. This research aims to identify the relationship pattern between GDP and Indonesian government domestic revenue using data from 2007-2011. The analysis was carried out through correlation and linear regression approaches to measure the level of relationship and form a predictive model between the two variables. The results show a significant positive correlation between GDP growth and increased government revenue. These findings are expected to contribute to supporting the formulation of macroeconomic policies based on empirical data.